Pengembangan Big Book Moderasi Beragama Berbasis Konsep Pratyaksa Pramana di Taman Kanak Kanak - Septiari Dewi, Putu Ayu; Wiranata, I Gusti Lanang Agung; Tria Ariani, Nyoman Wiraadi; Jayadiningrat, Made Gautama; Saraswati Dewi , Ida Ayu Putu Putri (Jayapangus Press, 2024)
This research highlights the importance of introducing the concept of religious moderation from an early age. Even though its implementation already exists in children's play activities, children are not yet fully aware of the concepts of tolerance, sharing and helping each other. Therefore, the Big Book of Religious Moderation based on the Pratyaksa Pramana concept was developed as a learning medium that introduces the concept of moderation through children's direct experience. This Book contains material on the concept of religious moderation based on the concept of Pratyaksa Pramana, which is knowledge experienced by children through direct experience. This research aims to introduce the concept of moderation to children, describe the development of the Book, and analyze the feasibility of its use through expert validation. The ADDIE development method was used in this research, involving teachers and children at the Taman Kurnia Denpasar Kindergarten as data sources. Data collection techniques using observation and checklist instruments. Data analysis was carried out using Lawshe's descriptive qualitative content validation formula, namely Content Validity Ratio (CVR). The research results show that this book is suitable for use, with a high CVI value of 0.5 and the final CVI calculation (average CVR) is 0.916667 indicating good content validity. The conclusion of the research in accordance with expert validation is that the use of the Big Book Religious Moderation media is very relevant and suitable for use with PAUD children because the material available in it is appropriate to the child's age development.